Attitudes of Norwegians towards the growing influence of English - Awedyk, Witosław (Wydawnictwo Naukowe UAM, 2009)
This paper shortly outlines the present status of English in Norway, principally in relation to the growing presence of English lexical borrowings in Norwegian. Some attention will also be devoted to the views held by Norwegian linguists towards the potential threat that the English language represents, particularly in domains where it is likely to supersede the Norwegian language.
Keywords: lexical borrowings; anglicisms; fornorsking; Norvagisering; Norwegianizing; language policy